Foreign direct investment, domestic investment and green growth in Nigeria: Any spillovers? - Akintoye Victor Adejumo; Simplice Asongu (African Governance and Development Institute (AGDI), 2019)
Globally, investments in physical and human capital have been identified to foster real economic growth and development in any economy. Investments, which could be domestic or foreign, have been established in the literature as either complements or substitutes in varying scenarios. While domestic investments bring about endogenous growth processes, foreign investment, though may be exogenous to growth, has been identified to bring about productivity and ecological spillovers. In view of these competing-conflicting perspectives, this chapter examines the differential impacts of domestic and foreign investments on green growth in Nigeria during the period 1970-2017. The empirical evidence is based on Auto-regressive Distributed Lag (ARDL) andGranger causalityestimates. Also, the study articulatestheprospectsforgrowth sustainability via domestic or foreign investments in Nigeria. The results show that domestic investment increases CO2 emissions in the short run while foreign investment decreases CO2 emissions in the long run. When the dataset is decomposed into three sub-samples in the light of cycles of investments within the trend analysis, findings of the third sub-sample (i.e. 2001-2017) reveal that both types of investments decrease CO2 emissions in the long run while only domestic investment has a negative effect on CO2 emissions in the short run. This study therefore concludes that as short-run distortions even out in the long-run, FDI and domestic investments has prospects for sustainable development in Nigeria through green growth.
Keywords: E23; F21; F30; O16; O55; 330; Investments; Productivity; Sustainability; Growth